Apical periodontitis in inflammatory bowel disease: a meta-analysis at patient and tooth level - La Rosa, Giusy Rita Maria; Lorenzo-Pouso, Alejandro Ismael; Caponio, Vito Carlo Alberto; Puci, Mariangela Valentina (Frontiers in Dental Medicine, 2025)
Apical periodontitis (AP) is the local inflammation of periapical tissues originating from the dental pulp disease. Cumulative evidence suggests a link between oral and gastro-intestinal systems in both health and disease. In this context, the relationship between AP and inflammatory bowel diseases (IBDs) has not yet been elucidated. The aims of this systematic review and meta-analysis were to describe the prevalence of AP in patients with IBDs and evaluate the potential association between AP and IBDs. Electronic (Embase, PubMed, Scopus, Web of Science) and manual literature searches were conducted from inception to 31 October, 2023 (updated in August, 2024). Strict inclusion criteria were applied to identify observational and experimental clinical studies on AP in IBDs patients. The bias risk was assessed using the Joanna Briggs Institute critical appraisal tools and a biases' report selected from the Oxford Centre for Evidence Based Medicine Catalogue of Bias. A meta-analysis was performed to determine the pooled prevalence and risk of AP at individual and tooth level and the quality of evidence was assessed by the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. The search strategy identified 82 articles with 5 studies included (657 subjects, 7,142 teeth). The overall proportion of AP was 58% at patient level (95% CI = 37%–78%, I2 = 95.3%) and 7% at tooth level (95% CI = 2%–15%; I2 = 99.2%). AP was prevalent in IBDs subjects than in healthy controls, both at patient and tooth level. The pooled OR was 1.57 (95% CI = 1.04–2.35; P = 0.038; I2 = 20%) at patient level, and 1.91 (95% CI = 1.16–3.15; P = 0.011; I2 = 82%) at tooth level. A potential association between AP and IBDs is plausible, although the quality evidence was low to very low. Longitudinal and experimental studies should be conducted to better understand the relationship between these two conditions and explore any potential causative factors. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=411038, PROSPERO (CRD42023411038).